STUDENTS' BEHAVIOR IN SEARCHING INFORMATION AT ISLAMIC CENTER LIBRARY - Siregar, Ihza Nabila; Batubara, Abdul Karim (Academic Solution Publisher, 2023)
This article discusses the search patterns for students in the Islamic Center Islamic Boarding School library. The aim of this research is to find out how students search for information in the Islamic boarding school environment and what obstacles they face when looking for information. The research method in this research is descriptive qualitative, namely research that aims to understand the phenomena experienced by research subjects, for example behavior, perceptions, motivation, actions, and so on. Furthermore, the data collection methods used were interviews, observation and documentation. In this research, the informants were 6 students of the Medan Islamic Center Islamic Boarding School who were in grade 12 and who had outstanding achievements. The research results show that Islamic Center Islamic Boarding School students carry out an information search process through six stages, namely, initiation, selection, exploration, formulation, collection and presentation. This research concludes that the research results show that Islamic Center Islamic Center Islamic Boarding School students carry out an information search process through six stages, namely, initiation, selection, exploration, formulation, collection and presentation. This research concludes that Islamic Center Islamic Boarding School students have an awareness of the need for information because they receive assignments. from ust and usth, then, then they were encouraged to look for information in the library by first recording in a small book the information they were looking for. Next, the students go straight to the collection shelf and collect the books they need, then read the table of contents to focus on the information they need. And write down the information you have read in a notebook. The next obstacle for students in searching for information is the lack of information search tools.